How Do Employers View People with Disabilities in the Labour Market? - Beaton, Ann M.; Kabano, John; Léger, Mélanie (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2012)
The object of this study was to examine how employers view people with disabilities in the labour market. Previous work had shown that employers maintain some perplexing views. Although they report positive attitudes toward people with disabilities in the workplace, these attitudes are not associated with the hiring practice of employers (Chan et al., 2010). To address this issue, researchers called upon the concept of aversive disablism (Deal, 2007). A total of 64 employers from New Brunswick and Quebec participated in an interview. Drawing from Social Representation Theory (Moscovici, 1973), findings revealed a system of common understanding that serves to limit the participation of people with disabilities to the paid labour force. Social representations of employers concerning people with disabilities in the workplace feature the demands of the market place, characteristics of employees with disabilities, inadequacies of the efforts designed to promote their inclusion in the workplace, and hiring decisions. Implications of these findings for the employment of people with disabilities are discussed.